Barriers to statin use in the Philippines - Feliciano, Katrina T; Dychiao, Robyn Gayle K; Eala, Michelle Ann B; Paguio, Joseph Alexander; Guinto, Renzo R * (Elsevier, 2022)
Maja Marcus and colleagues (March, 2022)1 show that, between 2013 and 2019, 41 low-income and middle-income countries (LMICs) failed to meet the WHO targets for statin use in preventing cardiovascular disease. We write from the perspective of the Philippines—a southeast Asian LMIC, where cardiovascular disease has been the leading cause of death for the past 33 years.2 Challenges in health financing, health infrastructure, and health-service delivery are among the substantial barriers to increasing statin use in the country. We hope the Philippine can perspective inform policies that tackle issues surrounding statin use in other LMICs.